PENERAPAN TECHNOLOGY ACCEPTANCE MODEL PADA RANCANGAN BUKU ELEKTRONIK PANDUAN PERJALANAN WISATA SEJARAH KOTA BANDUNG - Bonita, Melissa Shasya; Susanto, Eko; Sutaji, Deddy Sobarna (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
Historical tourism resources are one of the comparative and comparative advantages of Bandung city to other tourist destinations in Indonesia. The special characteristic of historical tourism is that the power of narratives poses a broader need for means of interpretation in the form of travel guides. Through the application of Technology Acceptance Model (TAM), this applied research reveals the process of designing electronic guidebooks that can be used as a means of interpretation for historical tourism visitors in The City of Bandung. The method of design with descriptive writing pattern is used to produce research reports on the design of electronic guidebook products in Bandung. This applied study has gathered opinions from 132 respondents through the dissemination of questionnaires about the components of travel guidebooks in accordance with the concept of Technology Acceptance Model (TAM) which is then analyzed descriptively. This applied research has resulted in a travel guidebook product and an understanding that tourists have a need for travel guidebooks that are easy to use and useful for themselves.